Analysis of Learning Innovation Based on Multiple Intelligences (MI) Used in Teaching of Islamic Education - Khoeriah, Ibnaturrofi; Shohib, Muhammad Wildan; Nubail, Ahmad (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
The existence of a dichotomy for students in the classroom makes transferring knowledge from teachers to students an inequality that runs ineffectively due to the difference between intelligent and unintelligent students, especially in learning Islamic education. This study analyzes learning innovations based on multiple intelligences (MI) in Islamic education subjects. This study is qualitative in nature, uses a library research approach, and the data analysis used is a descriptive-qualitative analysis. The data sources employed are from previous relevant research on multiple intelligence (MI)-based learning, such as international and national journals. However, Howard Gardner, a psychologist from Harvard University, adopted the study. This study revealed awareness that every student born into this world has their own uniqueness, which has the right to be recognized and appreciated in their learning environment and in developing their potential. Multiple intelligence (MI)-based learning is a form of learning innovation that can be an option for Islamic education teachers in Indonesia. Implementing multiple intelligences (MI)-based learning is intended to accommodate students' diverse intelligences.